2018
DOI: 10.1007/s13361-017-1869-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical-Molecular Distribution of EphrinA1 in Infarcted Mouse Heart Using MALDI Mass Spectrometry Imaging

Abstract: EphrinA1 is a tyrosine kinase receptor localized in the cellular membrane of healthy cardiomyocytes, the expression of which is lost upon myocardial infarction (MI). Intra-cardiac injection of the recombinant form of ephrinA1 (ephrinA1-Fc) at the time of ligation in mice has shown beneficial effects by reducing infarct size and myocardial necrosis post-MI. To date, immunohistochemistry and Western blotting comprise the only experimental approaches utilized to localize and quantify relative changes of ephrinA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…We used MALDI-TOF MSI technology to detect the distribution of phospholipid molecules in the brains of pMCAO rat models, which was very important for our study of the effect of NBP on the brain. 25 We found that PA (16:0/18:1), PA We demonstrated that NBP can reduce inflammatory damage, maintain immune tolerance, improve vascular density, and promote nerve cell regeneration through mechanisms that are shown in Fig. 5.…”
Section: Discussionmentioning
confidence: 69%
“…We used MALDI-TOF MSI technology to detect the distribution of phospholipid molecules in the brains of pMCAO rat models, which was very important for our study of the effect of NBP on the brain. 25 We found that PA (16:0/18:1), PA We demonstrated that NBP can reduce inflammatory damage, maintain immune tolerance, improve vascular density, and promote nerve cell regeneration through mechanisms that are shown in Fig. 5.…”
Section: Discussionmentioning
confidence: 69%
“…Depending on the analyte of interest, the protocol can include washing and/or digestion steps. Washing steps reduce ion suppression by the removal of salts, small molecules, and/or lipids [ 28 , 29 ]. Therefore, these steps are used for protein/peptide and in general not for lipid and or metabolite imaging.…”
Section: Mass Spectrometry Imaging In Cardiovascular Diseasesmentioning
confidence: 99%
“…Commonly used matrices for peptide and protein MSI are DHB, CHCA, and sinapinic acid (SA) [ 12 , 13 , 26 , 28 , 34 , 47 , 56 59 ]. A MALDI TOF-TOF is the most frequently used instrument for peptide and protein MSI for cardiovascular diseases, operated in positive ion mode with a range up to 30 kDa [ 12 , 13 , 26 , 28 , 34 , 47 , 56 , 60 ]. Linear mode was mostly used to enhance the signal of high-mass molecules, while the reflectron mode was used for small proteins and peptides.…”
Section: Application Of Peptide and Protein Msi To Cardiovascular Dismentioning
confidence: 99%
See 2 more Smart Citations